A European arena for joint innovation in healthcare: The Platform for Innovation of Procurement and Procurement of Innovation (PiPPi) - Andrews, Margaret R.; Long, Preston A.; Ahlberg, Martina; Balvert, Fred; Alessandrello, Rossana; Lazzari, Agnese; Timmermann, Maarten M.; Nouri Janian, Mariet; Rantaniska, Minerva; Spence, Ann; Söderman, Peter; Valls-Comamala, Victòria; et al. (Frontiers in Public Health, 2023)
By 2000 the European Union (EU) had recognized that its innovation capacity was underperforming in comparison to similar competitors and trading partners. Although the EU has made an effort to stimulate public research and development (R&D) through policy tools like Pre-Commercial Procurement (PCP) and Public Procurement of Innovation (PPI), starting with the 2000 Lisbon strategy and continuing through the 2021 updated Guidance on Innovation Procurement, there has remained a gap in knowledge of and use of these tools, in particular within healthcare. The past decades have seen an explosion in the number and use of digital technologies across the entire spectrum of healthcare. Demand-driven R&D has lagged here, while new digital health R&D has largely been driven by the supply side in a linear fashion, which can have disappointing results. PCP and PPI could have big impacts on the development and uptake of innovative health technology. The Platform for Innovation of Procurement and Procurement of Innovation (PiPPi) project was a Horizon 2020-funded project that ran from December 2018 to May 2022 with a consortium including seven of Europe’s premier research hospitals and the Catalan Agency for Health Information. To promote PCP and PPI, PiPPi established a virtual Community of Practice (CoP) that brings together all stakeholder groups to share and innovate around unmet healthcare needs. This perspective presents a brief history of PCP and PPI in Europe with a focus on digital innovation in healthcare before introducing the PiPPi project and its value proposition.